The Great university debate '88 [videorecording]. (Quezon City GMA Radio Television News and Public Affairs, 1988)
A debate on the issue : resolved that the U.S. military bases be removed after 1991, with the U.P. College of Law taking the affirmative side and the Ateneo School of Law the negative side.
Host, moderator, Ric Puno, Jr
Keywords: Military bases, American -- Philippines; Public speaking